Tuturan Do’omba dalam Adat Perkawinan Masyarakat Muna di Desa Kombunga Kecamatan Lasalepa Kabupaten Muna - Rizal Suprianti; Syahrun Syahrun; Nurtikawati Nurtikawati (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2024)
The purpose of this study is to describe the implementation process and meaning of the Do'omba Tradition in the marriage customs of the Muna Community in Kombungo Village, Lasalepa District, Muna Regency. The study used a qualitative research method. Data collection techniques were done by direct observation, interviews with 5 informants, and documentation. Data were analyzed in four stages, namely; (1) data collection, (2) data reduction, (3) data presentation, and (4) concluding. The results of this study are; (1) The Do'omba tradition procession in Kombungo Village begins at the Nopali stage, then Mpali-mpali (walking) the first visit of a boy with his parents, a discussion carried out by the man's family to determine the day before leaving for a girl's house, then at the Do'omba stage where the toko or traditional delegation that has been entrusted by the man's family goes to the woman's family house according to the promise referred to at the time of Kafoepe (news bearer/promise). (2) The tradition of Do'omba/Do'ombaghomo Patudhundo (stating intentions) means Defenagho Tungguno Karete (asking the guardian of the yard), which has the meaning of a traditional meeting where the man expresses his intentions with a sincere, honest heart and his seriousness in marrying a girl with a figurative question that is beautiful to hear for the woman, namely whether or not there is a guardian/companion for the girl who is going to be proposed to.